2011
DOI: 10.1093/hmg/ddr044
|View full text |Cite
|
Sign up to set email alerts
|

Maternal methyl-donor supplementation induces prolonged murine offspring colitis susceptibility in association with mucosal epigenetic and microbiomic changes

Abstract: Developmental epigenetic changes, such as DNA methylation, have been recognized as potential pathogenic factors in inflammatory bowel diseases, the hallmark of which is an exaggerated immune response against luminal microbes. A methyl-donor (MD) diet can modify DNA methylation at select murine genomic loci during early development. The components of the MDs are routinely incorporated into prenatal human supplements. Therefore, we studied the effects of maternal MD supplementation on offspring colitis susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 34 publications
4
109
1
Order By: Relevance
“…These findings have important implications, as the only known effective prevention against NTDs, including those induced by maternal diabetes (50), is folic acid supplementation. Recently, it was reported that folic acid supplementations during pregnancies produce increased incidences of breast cancers in mouse models (27) and inflammatory bowel diseases in the offspring (39). Therefore, there is an urgent and critical need for alternate candidates for preventing NTDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have important implications, as the only known effective prevention against NTDs, including those induced by maternal diabetes (50), is folic acid supplementation. Recently, it was reported that folic acid supplementations during pregnancies produce increased incidences of breast cancers in mouse models (27) and inflammatory bowel diseases in the offspring (39). Therefore, there is an urgent and critical need for alternate candidates for preventing NTDs.…”
Section: Discussionmentioning
confidence: 99%
“…Folate supplements are able to prevent about 70% of NTDs in human (47) and reduce maternal diabetes-induced NTDs in animal models (50). However, recent studies suggest that high maternal folate supplementation during pregnancy may increase the risk of breast cancer (27) and inflammatory bowel diseases (39) in offspring. Studies have shown that inositol can prevent some of the folate-resistant NTDs (16).…”
mentioning
confidence: 99%
“…This reconstitution is likely sensitive to the genetic background of the host and may be responsive to nutritional exposures (such as folate supplementation) during specific stages of development. 32 In summary, our manuscript emphasized the sophisticated network of molecular and cellular interactions that bridge genotype to phenotype in mammalian "superorganisms". This intercalating network has the capacity to overcome significant genetic/environmental insults (such as the homozygous absence of Tlr2 in mice) with no obvious phenotype change under usual environmental conditions.…”
Section: The Remarkable Adaptation Of the Colonic Mucosa To Toll-likementioning
confidence: 94%
“…This intricacy is probably most astounding in humans where the "superorganism" can be envisioned as the result of the multiorganic articLe addenduM articLe addenduM 1b). [30][31][32] Not surprisingly, plasma folate levels have been related to fecal bacterial composition changes in pregnant women recently. 33 These studies on one single vitamin/micronutrient model and illustrate the close to incomprehensible complexity of host-environment interactions in the human "superorganism".…”
Section: Adaptation To Physiologic Changes In the Gut And Its Microbesmentioning
confidence: 99%
“…Methyl-donors are abundant in human maternal dietary supplements. In mice, maternal methyl-donor supplementation augmented susceptibility to colitis in offspring, parallel to colonic mucosal DNA methylation and expression changes, followed by a sustained effect of the diet on colonic mucosal microbiota [185]. Although similar data in humans is missing, a study on ileal CD patients has found that several of the known CD risk gene loci were enriched in methylation compared to healthy controls, including the Th17 pathway and NOD2 [186].…”
Section: Epigeneticsmentioning
confidence: 99%